2008
DOI: 10.7326/0003-4819-148-1-200801010-00190
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: Effect of Monotherapy and Combination Therapy with Inhibitors of the Renin–Angiotensin System on Proteinuria in Renal Disease

Abstract: The ARBs reduce proteinuria, independent of the degree of proteinuria and of underlying disease. The magnitude of effect is similar regardless of whether the comparator is placebo or calcium-channel blocker. Reduction in proteinuria from ARBs and ACE inhibitors is similar, but their combination is more effective than either drug alone. Uncertainty concerning adverse effects and outcomes that are important to patients limits applicability of findings to clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
367
0
31

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 658 publications
(410 citation statements)
references
References 72 publications
12
367
0
31
Order By: Relevance
“…Small trials had reported greater reductions in proteinuria and even slowing of renal dysfunction in patients treated with combined therapy as compared to monotherapy. 61 The enthusiasm for this approach was dampened by the ONTARGET (Ongoing Telmisartan Alone and in combination with Ramipril Global Endpoint Trial) in which the combination therapy arm showed worse renal outcomes (doubling of the SCr and the need for dialysis), as compared with either of the monotherapy arms. 62 Thus, unless new data emerge supporting the use of dual therapy with ACEi and ARBs, monotherapy with either agent will remain the first-line for patients with DN.…”
Section: Blood Pressure Controlmentioning
confidence: 99%
“…Small trials had reported greater reductions in proteinuria and even slowing of renal dysfunction in patients treated with combined therapy as compared to monotherapy. 61 The enthusiasm for this approach was dampened by the ONTARGET (Ongoing Telmisartan Alone and in combination with Ramipril Global Endpoint Trial) in which the combination therapy arm showed worse renal outcomes (doubling of the SCr and the need for dialysis), as compared with either of the monotherapy arms. 62 Thus, unless new data emerge supporting the use of dual therapy with ACEi and ARBs, monotherapy with either agent will remain the first-line for patients with DN.…”
Section: Blood Pressure Controlmentioning
confidence: 99%
“…En estudios previos y un metaanálisis se ha demostrado que la asociación de un iECA con un ARA-2 logra reducir la proteinuria en mayor medida que cada droga por separado 1 .…”
Section: Introductionunclassified
“…El presente artículo es un análisis crítico del reporte parcial del estudio ONTARGET (The Ongoing Telmisartan Alone and in Combination with Ramipril Global Endpoint Trial) 1 , que se centra en los outcomes renales.…”
Section: Introductionunclassified
“…Based on these results, it is proposed that a combination of an ACE-inhibitor with an Ang II receptor antagonist could achieve a more complete blockade of the RAS than either therapeutic approach alone and a recent meta-analysis has confirmed the superiority of the combination over individual therapies in reducing proteinuria with only a minor impact on BP control. 33 Very recently, the results of the AVOID (Aliskiren in the eValuation Of proteinuria In Diabetes) study presented at the last meeting of the American Society of Nephrology 2007 showed that the addition of 300 mg of aliskiren, the first orally available direct renin inhibitor, on top of losartan 100 mg provides an additional 20% reduction in urinary albumin/creatinine ratio in patients with macroalbuminuria and diabetes suggesting once again that a more intensive blockade of the RAS system could provide additional renal protection. 34 However, there is also evidence that all antagonists do not provide the same degree of receptor blockade at least at the recommended starting doses.…”
Section: O P Y R I G H T J R a A S L I M I T E D R E P R O D U C Tmentioning
confidence: 99%